An Extended Hypofractionated Palliative Radiotherapy Regimen for Head and Neck Carcinomas - Laursen, Michael; Specht, Lena; Kristensen, Claus Andrup; Gothelf, Anita; Bernsdorf, Mogens; Vogelius, Ivan; Friborg, Jeppe (Frontiers in Oncology, 2018)
Background: Palliative radiotherapy to patients with head and neck cancer is often necessary, but there is a substantial variation in the treatment regimens reported in the literature, and consensus on the most appropriate schedules does not exist. In order to minimize acute toxicity while at the same time trying to achieve prolonged tumor control, a long hypofractionated regime has been used routinely in Denmark. In the current retrospective study we investigated the outcome in patients intended for palliative radiotherapy with this regime. Materials and methods: Patients with newly diagnosed head and neck cancer treated with palliative radiotherapy of 52-56 Gy in 13-14 fractions twice-weekly from 2009 to 2014 were included. Patients were excluded if they had previously received radiotherapy. Data on disease location, stage, patient performance status, treatment response, acute skin and mucosal toxicity, and late fibrosis were collected prospectively and supplemented with information from medical records. Results: Seventy-seven patients were included in the study. Fifty-eight patients (75 %) completed the intended treatment. Loco-regional tumor response (complete or partial) was evaluated two months post-treatment and observed in 45% of the entire population corresponding to 71% of patients alive. Performance status had a significant influence on survival (p=0.007) and on not completing the intended treatment. Grade III or IV acute mucositis were observed in 25 %, and grade III or IV acute dermatitis observed in 15 %. Conclusion: Palliative hypofractionated radiotherapy with 52-56 Gy in 13-14 fractions shows good tumor response and tolerability in a vulnerable patient population. However, it may not be suited for patients in poor performance status.